3D modeling of boron transport in DIII-D L-mode wall conditioning experiments. (March 2021) - Effenberg, F.; Bortolon, A.; Frerichs, H.; Grierson, B.; Lore, J.D.; Abrams, T.; Evans, T.E.; Feng, Y.; Lunsford, R.; Maingi, R.; Nagy, A.; Nazikian, R.; et al.
Abstract: DIII-D L-mode experiments with local boron powder injection for real-time wall conditioning have been interpreted for the first time with the 3D plasma edge transport Monte Carlo code EMC3-EIRENE. Local B sourcing in plasma scenarios with upstream densities 1 . 5 ⋅ 1 0 19 m −3 and 2.2 MW heating results in a non-axisymmetric B distribution in the scrape-off layer (SOL) and on the divertor. The SOL frictional flows at high plasma density cause a strong inboard drag of injected impurities ( ≈ 90 % ), while lower background plasma densities tend to result in a more uniform distribution. The thermal forces prevent B deposition in the near SOL while the frictional force causes B fluxes to cover the divertor plasma-facing components in a region 7–10 cm beyond the strike line. Radiative dissipation occurs for B influxes above 1 ⋅ 1 0 20 s −1 and causes a moderate, non-axisymmetric reduction of the far SOL divertor heat fluxes. A comparison of top and midplane B injection shows no substantial difference in inboard vs. outboard asymmetries of the B distribution. On the other hand, erosion or recycling at the strike line may distribute the boron more uniformly in the SOL. Highlights: First-time EMC3-EIRENE modeling of boron transport in DIII-D real-time wall conditioning experiments Modeling shows a 3D distribution of boron in the scrape-off layer (SOL) and divertor plasma Far SOL flows determine Boron deposition, ion thermal force in near SOL prevents B from reaching the strikeline Low density/collisionality plasmas and boron sputtering cause more even boron distribution in the divertor.